2019
DOI: 10.3310/hta23010
|View full text |Cite
|
Sign up to set email alerts
|

Faecal immunochemical tests versus colonoscopy for post-polypectomy surveillance: an accuracy, acceptability and economic study

Abstract: Background In the UK, patients with one or two adenomas, of which at least one is ≥ 10 mm in size, or three or four small adenomas, are deemed to be at intermediate risk of colorectal cancer (CRC) and referred for surveillance colonoscopy 3 years post polypectomy. However, colonoscopy is costly, can cause discomfort and carries a small risk of complications. Objectives To determine whether or not annual faecal immunochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(24 citation statements)
references
References 102 publications
(132 reference statements)
1
22
0
Order By: Relevance
“…Thus, the preservation of PPV for adenoma at low f-Hb thresholds and its improved performance over gFOBT, even at similar thresholds, indicates that FIT is likely to be more effective in preventing CRC than gFOBT. Removal of adenomas has been shown conclusively to reduce the incidence of CRC by RCTs of endoscopic screening, 30 and…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the preservation of PPV for adenoma at low f-Hb thresholds and its improved performance over gFOBT, even at similar thresholds, indicates that FIT is likely to be more effective in preventing CRC than gFOBT. Removal of adenomas has been shown conclusively to reduce the incidence of CRC by RCTs of endoscopic screening, 30 and…”
Section: Discussionmentioning
confidence: 99%
“…23 There are also strong parallels with studies looking at preferences for CC versus FIT in the symptomatic context. 24,25 Furthermore, there is the observation that women had a higher tolerance for missed cancers before switching to CC. This finding was in line with previous research demonstrating that women report more pain during CC 26 and have a stronger preference for non-invasive CRC diagnostic modalities.…”
Section: Discussion Summarymentioning
confidence: 99%
“…Overall, we reaffirm our previous 2013 recommendation. A recent study [111] detailing 5946 post-polypectomy "intermediate-risk" patients (3 -4 adenomas < 10 mm, or 1 -2 adenomas with one ≥ 10 mm) aimed to assess the efficacy of three annual rounds of FIT versus colonoscopy surveillance at 3 years for detection of CRC and advanced adenoma. This study demonstrated that in these intermediate risk patients, annual FIT with low threshold levels for fecal hemoglobin (Hb) (10 μg/g) had a high sensitivity for the detection of CRC (three cumulative tests: sensitivity 91.7 % [95 %CI 73.0 -99.0], specificity 69.8 % [95 %CI 68.5 -71.1]).…”
Section: Fecal Immunochemical Testing (Fit)mentioning
confidence: 99%